Cookie-Jar Alarms: An Analysis of First-Grade Students' Gendered Conceptions of Engineers following a Programming Design Task - April Mitchell; Kimberly H. Lott; Colby Tofel-Grehl (MDPI AG, 2022)
Women remain underrepresented in engineering and broadening participation has recently become the focus of education reform efforts. Increased emphasis on K-12 engineering education calls for the design of learning environments and curricula that increase interest and conceptual understanding of engineering work, beginning in the early years of childhood. We seek to understand what works, for whom, in what contexts, how it works, and how engineering curricula can be improved to promote social justice. Here, we evaluate the impact of a curricular intervention designed to promote equity in elementary engineering education. The integrated STEM curriculum unit engages first-grade students in programming a cookie-jar alarm. Using a KIBO robot, students program a distance sensor to trigger the alarm and customize the sounds and flashing lights. Students' pre-/post-drawings of 'engineers at work' were used to elicit reflection in semi-structured interviews, and to assess changes in students' conceptions of engineering work following the curricular intervention. A mixed analysis of the data revealed students' conceptual understanding of engineering work improved following the two-week curricular intervention, regardless of gender. However, the girls in the study were more likely than boys to identify as an engineer following the programming design task. We discuss the students' self-reported explanations and elements of the intervention that may have facilitated conceptual change. We recommend that, to promote equity in engineering education, "gender-responsive" curricula are essential.